Low-Density Granulocytes Affect T-SPOT.TB Assay by Inhibiting the Production of Interferon-γ in T Cells via PD-L1/PD-1 Pathway - Rao, Jiayue; Su, Rigu; Peng, Yiping; Guo, Yang; Huang, Zikun; Ye, Yutao; Gao, Yujie; Liu, Jun; Zhang, Lu; Luo, Qing; Li, Junming (Frontiers in Microbiology, 2021)
Background: T-SPOT TB (T-SPOT) assay is widely used for detection of Mycobacterium tuberculosis infection that based on the detection of Mycobacterium tuberculosis-specific interferon-γ-secreting T cells (ISCs) in peripheral blood mononuclear cells (PBMCs). Recently, high frequencies of low-density granulocytes (LDGs) were found in the PBMCs of tuberculosis patients. Whether these LDGs affect the detection of T-SPOT has not been investigated. The impact of LDGs on T-SPOT assay and related mechanism were investigated in this study. Methods: The correlations between the frequencies of LDGs and the results of T-SPOT were analyzed. And, T-SPOT with LDGs-removed PBMCs and PBMCs with exogenous addition of LDGs were performed. The possible mechanism was explored by detecting the levels of negative immune regulatory molecules on LDGs. The impact of programmed death ligand 1 (PD-L1) on T-SPOT was evaluated and confirmed by function blocking with neutralizing antibody. Results: The positive rates of T-SPOT and ISCs in patients with low LDGs frequency were significantly higher than those with high LDGs frequency. Removal of LDGs or exogenous addition of LDGs significantly increased or decreased the ISCs and the positive rate of T-SPOT. And, the frequencies of interferon-γ-producing T cells were negatively correlated with the frequencies of LDGs. The expression of PD-L1 was significantly elevated on LDGs. Pretreatment of LDGs with anti-PD-L1 antibody significantly counteracted the impact of LDGs on T-SPOT. Treatment of PBMCs with anti-PD-L1 antibody resulted in comparable ISCs with that of LDG removal. Conclusions: LDGs can inhibit the production of interferon-γ in T cells and decrease the positive rated of T-SPOT assay via highly-expressed PD-L1.